Unlocking the narrow bandgap investigations of perovskite JHgF3 (J = Li, Na, and Rb) materials: Computational predictions for optoelectronic devices - Shahzad, Muhammad Khuram; Hussain, Shoukat; Kumar, Abhinav; Rekha, M.M.; Pattanayak, Binayak; Jayabalan, Karthikeyan; Pandey, Vivek Kumar; Oza, Ankit D.; Tirth, Vineet; Hussien, Mohamed; Sfina, N. (The Journal of physics and chemistry of solids, 2025)
In the current day, light control has become a significant issue that perovskite materials can help with. The physical properties of halide perovskite JHgF3 (where J = Li, Na, and Rb) materials are examined for this purpose utilizing the GGA-PBE exchange correlation-functional and first principle computations (CASTEP). The compounds are cubic in shape, with five atoms per unit cell, and their space group is Pm3 m (221). Calculations reveal that the band structure of JHgF3 (where J = Li, Na, and Rb) exhibits a semiconductor nature with band gaps of 0.44, 0.45, and 0.62 eV. Perovskite materials' band structure graphs, partial DOS, and density of states (DOS) all clearly demonstrate their semi conductive characteristics. The JHgF3 (J = Li, Na, and Rb) compound is evaluated on the based of its mechanical aspects, including modulus (B, E, G), Poisson's ratiosvp (0.37, 0.36, and 0.34), Pugh's ratio (3.54, 3.43, and 3.82), mechanical index (14.020, 6.001, and 1.788), Cauchy pressure (22.585, 23.806, and 18.322), and hardness H (1.044, 1.265, and 1.688). In order to identify the light-matter interactions, the optical characteristics of JHgF3 have also been investigated and assessed. The study looks at thermodynamic parameters such as Debye temperature, melting temperature, sound velocity, and compressibility. The physical characteristics of the materials under study indicate that JHgF3 is appropriate for use in optoelectronic gadgets and applications. •JHgF3 (J = Li, Na, and Rb) perovskites have been investigated using DFT.•Compounds are found to be energetically, mechanically and dynamically stable.•Achieved narrow bandgap, higher effective light absorption, for optoelectronics applications.